Self-Medication with Antimicrobials among Medical Students of Bangladesh during the COVID-19 Pandemic: A Cross-Sectional Study - Abbasy, Asma Akter; Johora, Fatema; Jeenia, Fatiha Tasmin; Begum, Farzana; Ferdoush, Jannatul; Sabiha, Kazi; Sakin, Saniad Ahmed; Hossain, Afzal (Journal of Brahmanbaria Medical College, 2026)
Background: The COVID-19 pandemic disrupted healthcare access globally, potentially increasing unsupervised antibiotic use. Self-medication with antimicrobials among medical students is of particular concern due to their future prescribing role and its implications for Antimicrobial Resistance (AMR). The objective of the study was to describe the pattern of antimicrobial use as self-medication among the undergraduate medical students of Bangladesh during COVID-19 pandemic. Materials and methods: A descriptive cross-sectional study was conducted from October 2020 to February 2021 among 4th-year MBBS students from 14 medical colleges (Five government, Nine non-government) in Bangladesh. Data were collected via a validated online questionnaire covering demographics, antimicrobial use without prescription and reasons for such practice. Results: Of 916 respondents, the prevalence of antimicrobial self-medication was 22.06%. Among these, 75.24% used a single drug, 16.83% used two drugs and 7.92% used three concurrently. Azithromycin was most frequently used (52.47% of self-medicators), followed by doxycycline (16.83%) and ivermectin (15.84%). Fever, sore throat and dry cough were the most reported symptoms. Conclusion: Despite medical training, a considerable proportion of students engaged in unsupervised antimicrobial use during the pandemic. Strengthened antimicrobial stewardship education is essential to address irrational prescribing habits early in medical careers. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 35-38